2015
DOI: 10.1016/j.bone.2014.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of Bisphosphonate-Related Osteonecrosis of the Jaw (BRONJ) patients with sitafloxacin: New strategies for the treatment of BRONJ

Abstract: BRONJ has become a well-known, occasionally severe side effect of bisphosphonate therapy, as well as a clinical problem. Although treatment recommendations exist, no standard therapy has yet been established for BRONJ. Also, these recommendations identify several limitations that prevent clinicians from confidently diagnosing BRONJ. The aim of the present study was to establish a treatment approach in which all patients with exposed, infected bone or intraoral/extraoral fistulas were treated with sitafloxacin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
1
26
0
7
Order By: Relevance
“…They found significantly more severe sclerosis in patients with BRONJ compared with the control group. It was also observed that the degree of sclerosis increased with the clinical stage of BRONJ, disagreeing with Hamada et al 38 Bone sclerosis, which is visualized as the loss of contrast definition between cortical bone and bone marrow space, 27,36 has been reported as the most significant early imaging sign of BRONJ. 16,19,27,29,30,36 It has been used as a criterion for non-exposed BRONJ because of its high prevalence at sites indicated by patients as symptomatic.…”
Section: Imaging Findingsmentioning
confidence: 76%
See 2 more Smart Citations
“…They found significantly more severe sclerosis in patients with BRONJ compared with the control group. It was also observed that the degree of sclerosis increased with the clinical stage of BRONJ, disagreeing with Hamada et al 38 Bone sclerosis, which is visualized as the loss of contrast definition between cortical bone and bone marrow space, 27,36 has been reported as the most significant early imaging sign of BRONJ. 16,19,27,29,30,36 It has been used as a criterion for non-exposed BRONJ because of its high prevalence at sites indicated by patients as symptomatic.…”
Section: Imaging Findingsmentioning
confidence: 76%
“…Other reports point to CT as the best examination for diagnosing BRONJ at early stages, since it has a higher definition and better performance than panoramic radiography. 27,30,36,38,42,43 Nevertheless, according to some authors, all patients under bisphosphonate therapy should initially undergo panoramic radiography and afterwards further examinations if needed. 37,44 For the early detection of BRONJ, Hamada et al 38 recommend CT analysis of cancellous bone radiodensity.…”
Section: Imaging Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors mainly include: injuries associated with treatment in dental surgery, use of mismatched prosthetic restorations, presence of bone exostosis, odontogenic inflammations, poor oral hygiene, coexisting diabetes, simultaneous chemotherapy and/or steroid treatment, malnutrition and smoking. [13][14][15] The route of BP administration has a great impact. The risk of BRONJ is greater for intravenous therapy (0.8-15%).…”
mentioning
confidence: 99%
“…Második stádium: Amikor az 1. stádium képéhez társul a területet övező lágy részek gyulladása és fájdalom. Harmadik stádium: A 2. stádium képéhez kapcsolódik minimum egy az alábbi súlyos elváltozások közül, úgymint patológiás csonttörés, extraoralis fi stula, a crista zygomaticoalveolaréig, a ramus mandibulaeig, az arcüregig vagy a mandibula bázisáig terjedő necrosis, radiológiailag kimutatható nagymértékű osteolysis [8]. A stádiumbeosztástól függően különböző konzervatív, illetve sebészi kezelési stratégiákat is ajánlanak, de ezzel kapcsolatban egységes állásfoglalás még nem született [4,9].…”
unclassified